Design and Construction of Special Tools for Rear Seal Removal and Installation on Komatsu Engine Flywheel Housing - Aryadi , Ari Aryadi; Budi, Budi Utomo Wisesa; Hamid, Hamid Nasrullah; Lucky Herlyana (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
This research focuses on the innovation of mechanical work aid design in the form of special tools specifically used to remove and install the rear seal on the flywheel housing of Komatsu diesel engines type SAA6D107E-1 and SAA4D95LE-3. One of the procedures that is still done manually and has high risk is the replacement of the rear seal on the flywheel housing. The purpose of using special tools is to gain efficiency in the removal and installation of the rear seal on the flywheel housing. The research method includes field observation, component measurement, 2D and 3D design, and direct field trials. The test results show that this tool can reduce the processing time from 55 minutes to 20 minutes. The use of these special tools helps technicians in increasing the work speed in removing and installing without causing damage to other components.